The chemistry of explosives - Akhavan, Jacqueline (Royal Society of Chemistry, 2011)
"The third edition of this popular book has been fully revised and updated and outlines the basic principles needed to understand the mechanism of explosions by chemical explosives. The history, theory and chemical types of explosives are introduced, providing the reader with information on the physical parameters of primary and secondary explosives. Thermodynamics, enthalpy, free energy and gas equations are covered together with examples of calculations, leading to the power and temperature of explosions."--P. [4] of cover.
Previous ed.: 2004.
Keywords: Explosives.; elektronické knihy; electronic books